Computing an Optimal Layout for Cone Trees - Dirk Zeckzer; Fang Chen; Hans Hagen (Scientific Visualization: Advanced Concepts, 2010)
Many visual representations for trees have been developed in information and software visualization. One of them are cone trees, a well-known three-dimensional representation for trees. This paper is based on an approach for constructing cone trees bottom-up. For this approach, an optimal layout for these trees is given together with a proof that based on the assumptions, there can be no better layouts. This comprises special cases, an optimal constant for the general case, and a post-processing step improving the layout.